Towards A Coherent Implementation Of Safe Building Laws And Regulations In Cameroon: Law, Governance And Institutional Imperatives - Tene, Claude Bernard; Omer, Siddig; Mempouo, Blaise (Journal of Sustainable Development Law and Policy, 2025)
Over the last decade, a sustained pattern of building collapse and fire outbreaks has been observed in various West African countries such as Cameroon, Nigeria and Ghana. This has become a matter of serious concern among building practitioners and the public authorities in these countries given the extensive loss of housing investment and human lives. The main reasons for the increased collapse of buildings include poor inspection and monitoring, structural defects, defective design/structure, illegal conversion and alterations and, most importantly, non-adherence to existing building regulations and laws. This article examines the scope of implementation and enforcement of safe building legislation and regulations in Cameroon. It identifies the existing national building regulations and the factors that limit their implementation. The article uses various data collected through questionnaires and interviews to support the finding that although there are extensive norms and regulations dealing with planning matters, there is a lack of technical building regulations and control in the country and that the existing regulations are not effectively implemented. Generic suggestions are made for a coherent implementation of current laws and regulation for safety in the construction industry.